Wheat (Triticum aestivum L.) Seed Germination under Salt Stress as Influenced by Priming - G. R. Mohammadi; S. Mozafari (2012)
The effect of priming on wheat seed germination under different salt stress levels was evaluated at the Seed Research Laboratory of Razi University, Iran. The experiment was a factorial with three factors arranged in a completely randomized design with three replications. The first factor was seed priming treatments [control (unprimed), distilled water, NaCl and HB-101 (a purely natural extract)], the second was salt stress levels (0.0, -0.3, -0.6, -0.9, -1.2 and -1.5 MPa) and the third was wheat cultivars (Sardari and Pishtaz). All of the traits under study, including seed germination percentage, mean germination rate, radicle length, plumule length, seedling dry weight, seedling vigor index and plumule relative water content, significantly declined when stress level was increased. Cv. Sardari performed better as salt stress was intensified. In general, primed seeds performed better than unprimed seeds especially under higher salt stress levels. Although there were no significant differences between the priming treatments for most of the traits under study, the seeds primed with HB-101 performed better in some cases. Under salt stress condition, seed priming especially with HB -101 can be used as an efficient method to alleviate the harmful effects of salinity on wheat during the seed germination process.
Keywords: Wheat--Yields.; Germination